Academic freedom, institutions and productivity - Niclas Berggren; Christian Bjørnskov (Research Institute of Industrial Economics (IFN), 2021)
The issue of what explains differences in the wealth of nations is one of the most classic in economics. We propose de facto academic freedom as an explanatory variable. The main idea is that such freedom allows for the development of new useful knowledge through research unconstrained by powerholders in business and politics. Using a new global panel-data set, encompassing up to 127 countries over the period 1960-2015, we show that there is indeed a positive relationship between de facto academic freedom and both labor and total-factor productivity growth. However, this effect only appears as long as the quality of the legal system is sufficiently high. We suggest that this is because such institutional quality offers protection that stimulates entrepreneurs to make use of the new knowledge produced in academia in innovative activities, which in turn benefits productivity growth.
Keywords: F13; H25; O31; O38; O43; 330; Institutions; Academic freedom; Freedom of speech; Productivity; Growth